HUBUNGAN ANTARA VISKOSITAS DARAH DENGAN FUNGSI KOGNITIF PADA LANSIA - Rahayu Andiyani,* Hexanto Muhartomo,* Dwi Pudjonarko* (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION VISCOSITY PLAYS AN IMPORTANT ROLE IN COGNITIVE FUNCTION THROUGH HEMORHEOLOGICAL CHANGE CEREBRAL MICROEMBOLI AND ATHEROSCLEROSIS PREVIOUS STUDIES HAVE EXAMINED THE ASSOCIATION BETWEEN BLOOD AND PLASMA VISCOSITY AND COGNITIVE FUNCTION USING A VARIETY OF INSTRUMENTS